Potassium Effects on NCC Are Attenuated during Inhibition of Cullin E3–Ubiquitin Ligases - Sathish K. Murali; Robert Little; Søren B. Poulsen; Mohammed Z. Ferdaus; David H. Ellison; James A. McCormick; Robert A. Fenton (Cells, 2021)
The thiazide-sensitive sodium chloride cotransporter (NCC) plays a vital role in maintaining sodium (Na+) and potassium (K+) homeostasis. NCC activity is modulated by with-no-lysine kinases 1 and 4 (WNK1 and WNK4), the abundance of which is controlled by the RING-type E3 ligase Cullin 3 (Cul3) and its substrate adapter Kelch-like protein 3. Dietary K+ intake has an inverse correlation with NCC activity, but the mechanism underlying this phenomenon remains to be fully elucidated. Here, we investigated the involvement of other members of the cullin family in mediating K+ effects on NCC phosphorylation (active form) and abundance. In kidneys from mice fed diets varying in K+ content, there were negative correlations between NCC (phosphorylated and total) and active (neddylated) forms of cullins (Cul1, 3, 4, and 5). High dietary K+ effects on phosphorylated NCC were attenuated in Cul3 mutant mice (CUL3-Het/Δ9). Short-term (30 min) and long-term (24 h) alterations in the extracellular K+ concentration did not affect cullin neddylation levels in ex vivo renal tubules. In the short term, the ability of high extracellular K+ to decrease NCC phosphorylation was preserved in the presence of MLN4924 (pan-cullin inhibitor), but the response to low extracellular K+ was absent. In the long term, MLN4924 attenuated the effects of high extracellular K+ on NCC phosphorylation, and responses to low extracellular K+ were absent. Our data suggest that in addition to Cul3, other cullins are involved in mediating the effects of K+ on NCC phosphorylation and abundance.